2019
DOI: 10.1002/berj.3523
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between implicit theories of intelligence, attainment and socio‐demographic factors in a UK sample of primary school children

Abstract: Research emerging from the USA suggests that holding an incremental theory of intelligence (growth mindset) has a positive impact on academic success. However, limited empirical work has explored this relationship in a UK sample, and there has been a lack of research into the antecedents which might influence the development of certain intelligence beliefs. This study aimed to explore these gaps in the existing literature. Data was collected from 710 9‐year‐old pupils (UK Year 5). Participants completed attain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 43 publications
1
5
0
1
Order By: Relevance
“…This study also revealed that the students in the lower academic track were at risk in two ways. On the one hand, when compared with students in the higher academic track, they more frequently reported having a fixed mindset about SRL, which confirmed previous results concerning how at-risk students have a relatively fixed view of mindsets of intelligence (Warren et al, 2019). Simultaneously, we also found that academic track as a factor negatively correlated with strategy knowledge, which means that the students from the lower academic track possessed less strategy knowledge than their peers in the more academically demanding track did.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…This study also revealed that the students in the lower academic track were at risk in two ways. On the one hand, when compared with students in the higher academic track, they more frequently reported having a fixed mindset about SRL, which confirmed previous results concerning how at-risk students have a relatively fixed view of mindsets of intelligence (Warren et al, 2019). Simultaneously, we also found that academic track as a factor negatively correlated with strategy knowledge, which means that the students from the lower academic track possessed less strategy knowledge than their peers in the more academically demanding track did.…”
supporting
confidence: 89%
“…When focusing on students' genders, researchers have observed null or mixed gender differences in domain-general mindsets about intelligence (Compagnoni et al, 2019;Warren et al, 2019). Hertel and Karlen (2020) found no correlation between gender and mindsets about the malleability of SRL in a sample of university students.…”
Section: Gender Age and Academic Track As Covariates Of Self-regulated Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who hold an incremental theory about intelligence (more recently described as a growth mindset) believe that change in intelligence is possible, whereas individuals who hold an entity theory about intelligence (fixed mindset) view intelligence as a fixed trait (Dweck and Leggett, 1988;Dweck, 2006). Compared to a fixed mindset, growth mindset relates to various adaptive academic behaviors and better academic performance (Yeager and Dweck, 2012;Claro et al, 2016;Warren et al, 2019). Considering the positive association between children's growth mindset and their academic outcomes, it is imperative to investigate the origins and sources of children's beliefs as they develop during early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…Implicit Theories of Intelligence have been shown to have consequences for academic performance and persistence, with some evidence suggesting that holding an incremental theory has a positive impact on academic success (e.g. Blackwell, Trzesniewski & Dweck, 2007;Warren et al, 2019) and other replications (Li & Bates, 2020) and meta-analyses (Sisk, Burgoyne, Sun, Butler & Macnamara, 2018) not.…”
Section: Introductionmentioning
confidence: 99%